2011
DOI: 10.1097/tld.0b013e318227fd19
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Support Needs of Individuals With Autism Spectrum Disorders

Abstract: This article outlines some of the factors leading to challenges in succeeding in college environments for individuals with autism spectrum disorders (ASD). Individuals with the intellectual ability to pursue postsecondary education still need individualized and ongoing supports from their families and others to ensure success. Social challenges may impede integration into college, but other factors related to executive functioning and higher order planning are also critical. Suggestions for program planning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 9 publications
0
22
1
Order By: Relevance
“…This terminology distinguishes the programme from the type of supports many students have received for most of their lives and reflects our attempts to involve the students as collaborators in gaining a new skill set better suited for the academic and social expectations of a university setting. As already noted, Hewitt (2011) reported that the college students with whom she has worked have presented with both social communication deficits and executive functioning deficits. Her observations matched our own and thus our students receive supports in both areas unless an individual student demonstrates adequate abilities in one or the other area.…”
Section: A Description Of the Communication Coaching Programme (Ccp)mentioning
confidence: 85%
“…This terminology distinguishes the programme from the type of supports many students have received for most of their lives and reflects our attempts to involve the students as collaborators in gaining a new skill set better suited for the academic and social expectations of a university setting. As already noted, Hewitt (2011) reported that the college students with whom she has worked have presented with both social communication deficits and executive functioning deficits. Her observations matched our own and thus our students receive supports in both areas unless an individual student demonstrates adequate abilities in one or the other area.…”
Section: A Description Of the Communication Coaching Programme (Ccp)mentioning
confidence: 85%
“…SR is closely related to executive functioning capacity (e.g., one’s ability to update and monitor information, inhibit prepotent responses; Bridgett et al 2013) and ability to regulate one’s emotions, or adapt and modify one’s emotional response in the service of identified goals (i.e., goal-directed behavior; Bridgett et al 2013; Thompson 1994). Problems with SR, including executive function and emotion regulation impairments, are commonly ascribed to individuals with ASD (Corbett et al 2009; Hewitt 2011; Mazefsky and White 2013). These deficits can be related to a host of problems such as inflexibility in routines, poor inhibitory control and time management, amotivation or impaired goal-directed behavior (e.g., Jahromi et al 2009).…”
Section: Development Of the Steps Programmentioning
confidence: 99%
“…It is important to recognize the huge differences between secondary and postsecondary contexts, as failure to do so may place a student at risk (Hewitt, 2011). As the complex neuroscience underlying ASD becomes clearer (Williams et al, 2013;Williams, Minshew, & Goldstein, 2015), the need for supports even among many who appear on the surface to be well prepared for college also has become clearer.…”
Section: Discussionmentioning
confidence: 99%
“…Such deficits may have a significant impact on college success (Hewitt, 2011). The first year of college involves adjusting to novel environments and much lower structure than that in high school.…”
Section: Cognitive Areas Supporting Communicationmentioning
confidence: 99%